If H+H=G, 2H=G.
G+F also equals G. That means 2H=G+F
E*H=E. The only possible solution here for H is 1.
So H=1.
2H=G+F. Substitute H for 1.
2(1)=G+F. When you distribute, it's:
2=G+F
In the original equation, H+H=G. That means 1+1=G, so G=2.
G+F=G. Substitute G for 2.
2+F=2. Therefore, F=0.
And E can be any number. We don't have enough info to found out what it is.
2007-11-21 11:57:50
·
answer #1
·
answered by Aint No Bugs On Me 4
·
0⤊
0⤋
1 + 1 = 2
5 x 1 = 5, 3 x 1 = 3, 4 x 1 = 4, 6 x 1 = 6, 7 x 1 = 7, 8 x 1 = 8,
9 x 1 = 9
2 + 0 = 2
2007-11-21 11:58:55
·
answer #2
·
answered by sv 7
·
0⤊
0⤋
e* h = e is only true if e = 0 or h = 1
g + f = g is only true if f=0
h + h = g if h = 1 then g = 2
so h = 1 , g = 2 , f = 0
there is no way to find E
if we use e = 0 for e* h = e ( 0 * h = 0) then we cant solve for h or g
2007-11-21 12:07:27
·
answer #3
·
answered by mark 6
·
0⤊
0⤋
E x H = E, therefore, I would presume H = 1
From this, you find that G = H+H = 1+1 = 2
I agree with your presumption that G+F=G, so F = 0
But there is no way to prove the value of E (unless E = 0), then H could be any value that is 1/2 of G.
2007-11-21 11:58:14
·
answer #4
·
answered by David M 4
·
1⤊
0⤋
if F is a 0... H has to be 1. E can be any number 1-9.
G is 2
sorry if this is wrong but this is how i figured it...hope this helps
2007-11-21 11:57:13
·
answer #5
·
answered by luna d 1
·
0⤊
0⤋
G=2
H=1
E=1
F=0
2007-11-21 11:55:02
·
answer #6
·
answered by wolverines189 3
·
0⤊
1⤋
H = 1
G = 2
E = any number
F = 0
2007-11-21 11:55:26
·
answer #7
·
answered by meg 2
·
2⤊
0⤋
2H = G
E = HE
G = F+G
F = 0
H = 1
if H = 1, then G = 2
can't find E.
all you can do is say E= E and since that is true, E could be anything.
2007-11-21 11:57:00
·
answer #8
·
answered by sayamiam 6
·
0⤊
0⤋
You can let E, H, G, and F be 0. ^_^
2007-11-21 11:58:21
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
F=0
H=1
G=2
E= any other one digit number
2007-11-21 11:57:34
·
answer #10
·
answered by Tros 2
·
0⤊
0⤋